A Three‐Component Organometallic Tyrosine Bioconjugation. Issue 11 (9th February 2018) - Ohata, Jun; Miller, Mary K.; Mountain, Courtney M.; Vohidov, Farrukh; Ball, Zachary T.
Abstract: Metal‐based bioconjugation linkages represent a little‐studied approach to protein functionalization that provides novel reactivity, stability, and function. Described is an organometallic bioconjugation, employing rhodium(III) salts, to link boronic acids with tyrosine residues by an arene complex. Both peptides and proteins are amenable to the mild bioconjugation in aqueous media, allowing incorporation of useful functionalities, such as affinity handles or fluorophores. Because of the metastability of the inorganic linkage, the conjugates are susceptible to cleavage by nucleophilic redox mediators but are stable toward typical biological conditions. Abstract : Linked : Rhodium(III) salts, in the presence of boronic acids, form organometallic arene complexes at tyrosine residues. The rhodium linkage allows protein functionalization that is stable to biological conditions. DTT=dithiothreitol.